INVESTIGATION OF THE DIFFUSION FLAME - MAO, N. S. (Periodica Polytechnica Mechanical Engineering, 1990)
In this paper, the analysed problem is how to explain the geometrical structure of flames in the combustion chamber, and how to establish the relationship between geometrical characteristics and flow parameters at the burner orifice. On the basis of our experimental data we have made a regression analysis to present numerical equation for practical use.